The Impact of Bank and Non-Bank Financial Institutions on Local Economic Growth in China - Xiaoqiang Cheng; Hans Degryse (Katholieke Universiteit Leuven, LICOS Centre for Transition Economics, 2006)
This paper shows that banking development spurs growth, even in a country with a high growth rate such as China. Employing data of 27 Chinese provinces over the period 1995-2003, we study whether the financial development of two different types of institutions ?banks and non-bank financial institutions ?have a (significantly different) impact on local economic growth. Our findings show that banks outperfirm non-bank financial institutions. Only banking development exerts a statistically and economically significant positive impact on local economic growth. This effect becomes more pronounced when the financial sector is less concentrated.
Keywords: E44; G21; 330; growth; financial development; Chinese provinces; banks; Bank; Finanzintermediär; Regionales Wachstum; Provinz; China